Clinical response to dabrafenib plus trametinib in BRAF V600E mutated papillary craniopharyngiomas: a case report and literature review - Hanona, Paul; Ezekwudo, Daniel; Anderson, Joseph (Frontiers in Oncology, 2024)
Papillary craniopharyngiomas are rare tumors prevalent to the precision oncology world due to their high rate of BRAF V600E mutations. Symptoms include vision loss, neuroendocrine dysfunction, and cognitive dysfunction. Treatment involves an interdisciplinary approach with surgery, radiation, and systemic treatment. Recent attention has been directed toward targeted therapy in this space, especially with targets to the BRAF V600E mutated pathway. Focusing on this pathway could solidify future standards of care treatment. A 61-year-old male came in with bilateral homonymous hemianopsia. This prompted a brain MRI that showed a bilobed centrally cystic peripherally enhancing sellar and suprasellar mass with mass effect on the left greater than right optic chiasm and nerves. He underwent a primary resection of the suprasellar cystic tumor, and it was revealed that he had papillary craniopharyngioma. Three months later, he represented with visual defects, and repeat MRI showed cystic recurrence with compression of the optic chiasm. He underwent an endonasal resection of the middle fossa tumor; pathology, this time, showed a BRAF V600E mutated papillary craniopharyngioma. Nine months later, another recurrence happened, and the patient was started on BRAF and MEK inhibitors: dabrafenib (75 mg BID) and trametinib (2 mg daily). The patient has had clinical improvement of visual symptoms and is currently continuing this treatment. He was last seen in October of 2024, and he is clinically stable. The use of targeted therapies is an evolving space for BRAF V600E mutated papillary craniopharyngiomas. This is a case showing improvement of a craniopharyngioma after treatment with BRAF and MEK inhibitor combinations. The role of BRAF and MEK inhibitor combinations continues to evolve in this space.